EFFECTIVE STRATEGIES IN PRODUCTION MANAGEMENT TO IMPROVE OPERATIONAL EFFICIENCY - Wahyuanto, Eko (MSJ : Majority Science Journal, 2025)
Operational efficiency is a key driver of competitiveness in modern manufacturing industries. This study aims to identify and synthesize effective production management strategies that have proven successful in enhancing operational performance. Using a systematic literature review approach, the study analyzes 15 relevant scientific publications from the past five years, covering both national and international contexts. Thematic analysis was employed to explore the interplay between process-based methods such as Lean Manufacturing, Value Stream Mapping (VSM), and 5S, and the adoption of digital technologies including big data analytics and digital twin systems. The results indicate that the integration of structured process strategies with digital innovation significantly contributes to improvements in production cycle efficiency, lead time reduction, and waste elimination. The findings also emphasize the need for adaptive strategies that align with the emerging principles of Industry 5.0 centered on sustainability, flexibility, and human-machine collaboration. Through a cross-study synthesis, this article contributes to the academic discourse by offering a conceptual foundation for developing resilient and contextually relevant production strategies in the digital transformation era.